Thermostimulated implantation of nanoscaled Ag particles into a quartz glass using a CO₂ laser beam - Ageev, L.A.; Miloslavsky, V.K.; Makovetsky, E.D.; Beloshenko, K.S.; Stronsky, A.V. (Functional Materials, 2007)
Coloration of fused quartz with colloidal silver (particle radius a≈3 nm) is realized by irradiation of thin (≈40 nm) granularr Ag film on a quartz plate by a continuous Gauss beam of CO₂ laser (λ = 10.6 μM, P = 30 W). Using the AFM microscopy, a relief of the colored surface has been revealed. It is formed by oval lugs with mean transversal size of about ≈ 0.2 μM and heights of several nanometers. The relief is created due to surface deformation caused by subsurface Ag granules. The measured absorption spectrum of the colloid has shown that the absorption band contour is similar to the Lorentz one, maximum being at ωm = 4.48-10¹⁵ s⁻¹, and half-width is γ = 0.714-10¹⁵ s⁻¹. Making use of Maxwell-Garnet theory, it has been found that for this colloid, the filling factor is q ≈ 0.05/0.10 and coloration depth h ≈ 100/50 nm.